CTCF, Cohesin, and Chromatin in Human Cancer - Sang-Hyun Song; Tae-You Kim (Genomics & Informatics)
It is becoming increasingly clear that eukaryotic genomes are subjected to higher-order chromatin organization by the CCCTC-binding factor/cohesin complex. Their dynamic interactions in three dimensions within the nucleus regulate gene transcription by changing the chromatin architecture. Such spatial genomic organization is functionally important for the spatial disposition of chromosomes to control cell fate during development and differentiation. Thus, the dysregulation of proper long-range chromatin interactions may influence the development of tumorigenesis and cancer progression.